The protected working capacity envelope concept an alternate paradigm for automated service provisioning. - Grover, W.D (IEEE Communications magazine)
At present we see only one basic approach being considered by implementors and standards organizations for provisioning of dynamic protected lightpath services that make efficient use of shared protection capacity. This is the paradigm of a primary working path protected end-to-end by a disjoint backup path using shared spare capacity. Sharing is arranged among the backup paths associated with other primary paths that are failure-disjoint from the current primary path. This approach called shared backup path protection (SBPP) has many advantages but also provides a great deal of network state information to be available and current in every node. It also makes the arrangement of protection a per-connection task, rather than user-selectable service option supported by the network itself. We propose an alternative paradigm for consideration, partly summed up as provisioning over protected capacity rather than provisioning protection. Under a given distribution of spare capacity, locally acting protection or restoration schemes create an "envelope" of protected working channels. Dynamic provisioning within this envelope is simplified to a shortest path routing problem and (depending on the mode of operation) requires little or no dissemination of state changes on a per-connection basis. We explain how existing "static" capacity design methods can be adopted to the dimensioning of such a working capacity envelope and the envelope dimensions further adapted online to track evolution of the overall pattern of random demand. An important property is that nothing needs to be done to arrange protection for services on the per-connection timescale other than routing the service itself. Arbitrarily fast-paced demand arrivals and departures can be accommodated within a static distribution of spare capacity. Adjustments to the envelope itself are required only on the timescale on which the statistical parameters of the random demand changes. This may provide an inherently more scalable, less database-dependent, and higher-availability alternative than SBPP, or at least an additional service modality that can be offered to customers.